(untitled) (Homiletic, 2025)
Preaching is often imagined as fearless proclamation—unmasking truth in the full light of day. Yet for many preachers, especially those navigating identity-based vulnerability, full self-revelation is neither safe nor possible. This article challenges the familiar dichotomy between pastor and prophet, arguing instead for a homiletic that honors both presence and concealment as interwoven expressions of faithful proclamation. Drawing from incarnational theology, kenotic Christology, performance theory, and queer and coming-out discourse, this study reframes strategic withholding not as a failure of authenticity but as a theological practice of love and wisdom. Through close readings of Scripture and historical exemplars—including Oscar Romero, Pauli Murray, and Dietrich Bonhoeffer—it explores how truth may be proclaimed through subtext, timing, gesture, and silence. In doing so, it proposes a model of preaching rooted in pastoral discernment and prophetic courage, where embodiment becomes proclamation, and discretion emerges as a Spirit-led mode of truth-telling.